2022
DOI: 10.24018/ejmed.2022.4.1.1171
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean Section Characteristics Based on Robson Classification at Sanglah Hospital

Abstract: Background: Improving maternal and child health can be achieved through programs aimed at reducing maternal mortality rate (MMR) and infant mortality rate (IMR). Apart from going through a normal delivery, labor can also be done by abdominal surgery/ cesarean section (CS). A safe and timely Cesarean Section (CS) remains a major challenge in countries with high MMR, which poses new challenges to these countries in being able to minimize CS without clinical indication. This study aims to determine the rates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…This shows that assessing changes to know the groups (Robson groups 5, 2A, and 1) that contribute to the prevalence of CS deliveries the most might give beneficial knowledge for decreasing CS rates and thus offers a standard for assessing the success of upcoming attempts to cut CS rates in Canada. Contrary to the findings of the previous investigation, Sugianto et al came to the conclusion that 34.3% of the 385 cases of labour involved CS [21]. Of this, the majority of the CS deliveries were in the women aged 25-29 years, primigravida women, and women without a history of prior CS; the primary gestational age was a term, and the biggest contribution of the CS rate of 23 Additionally, TGCS offers a method for gathering and analyzing data regarding CS rates in an institution.…”
Section: Konar Et Alcontrasting
confidence: 60%
See 1 more Smart Citation
“…This shows that assessing changes to know the groups (Robson groups 5, 2A, and 1) that contribute to the prevalence of CS deliveries the most might give beneficial knowledge for decreasing CS rates and thus offers a standard for assessing the success of upcoming attempts to cut CS rates in Canada. Contrary to the findings of the previous investigation, Sugianto et al came to the conclusion that 34.3% of the 385 cases of labour involved CS [21]. Of this, the majority of the CS deliveries were in the women aged 25-29 years, primigravida women, and women without a history of prior CS; the primary gestational age was a term, and the biggest contribution of the CS rate of 23 Additionally, TGCS offers a method for gathering and analyzing data regarding CS rates in an institution.…”
Section: Konar Et Alcontrasting
confidence: 60%
“….38% was from Robson group 10[21]. Furthermore, in a study byKonar et al, the Robson groups 1, 2, 3, and 5 were discovered to be the main drivers of the total CS rate[26].…”
mentioning
confidence: 95%
“…In other African countries, hospital-level CS rates varied from as low as 18.2% in Senegal (Mbaye et al, 2015), up to 25.7% in Ethiopia (Tura et al, 2018) and 42.4% in South Africa (Makhanya et al, 2015). In Asia, rates range from 20.3% in Oman (Kazmi et al, 2012), to 34.3% in Indonesia (Sugianto et al, 2022), 50.5% in India (Spandana and Shivanna, 2020) 55.5% in Thailand (Sukmanee et al, 2020), and 82% in for-profit facilities in Bangladesh (Begum, 2019). In Europe, a study in Lithuania (Kacerauskiene et al, 2017) reported a rate of 22.7%, rate was as low as 16.1% in Iceland and as high as 56.9% in Cyprus (Zeitlin et al, 2021).…”
Section: Hospital Level Caesarean Section Ratementioning
confidence: 99%
“…Few studies had been performed to assess the CS rate in large hospitals in Jakarta and Bali. They found that the CS rate in one hospital in Jakarta was 48.0% and in Bali 34.3%, much higher than the national average, i.e., 17.7% [10][11][12]. The most common indication for CS was preterm pregnancies, followed by malpresentation, and CS in previous pregnancy [10,11].…”
Section: Introductionmentioning
confidence: 99%